2017
DOI: 10.1111/trf.14124
|View full text |Cite
|
Sign up to set email alerts
|

Platelet lysate obtained via plateletpheresis performed in standing and awake equine donors

Abstract: Plateletpheresis using commercially available apheresis equipment is a feasible option for collecting platelet concentrate from equine donors. The lysate generated from the apheresis product contains growth factors and has potential to be used as a fetal bovine serum substitute for cell culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
(41 reference statements)
1
21
0
Order By: Relevance
“…TGF-β seems to be especially important for the synthesis of proteoglycans and collagen type II [ 54 , 55 ] and for the differentiation of MSCs into chondrocytes, a process that has been documented by measuring the chondrogenic-related transcriptional factor Sox9 and mRNA expression of collagen type II [ 56 ]. It is possible that the relatively high concentrations of TGF-β present in ePL [ 26 ] might have been responsible for favoring MSC chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF-β seems to be especially important for the synthesis of proteoglycans and collagen type II [ 54 , 55 ] and for the differentiation of MSCs into chondrocytes, a process that has been documented by measuring the chondrogenic-related transcriptional factor Sox9 and mRNA expression of collagen type II [ 56 ]. It is possible that the relatively high concentrations of TGF-β present in ePL [ 26 ] might have been responsible for favoring MSC chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of ePL was conducted as previously described [ 26 ]. Briefly, platelet concentrates were obtained following plateletpheresis (COBE Spectra Dual-Needle) performed in five mix-breed horses belonging to the University of Georgia equine blood donors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PL can be prepared in autologous or allogeneic forms, using platelets collected by apheresis or PRP method (Burnouf et al, 2013;Sumner et al, 2017). Autologous prepared PL lacks immune responses (Hemeda et al, 2014) and is used in clinical trials (Shih & Burnouf, 2015).…”
Section: Preparation Of Plmentioning
confidence: 99%
“…Growth factors and chemokines include transforming growth factor β (TGF-β), brain-derived neurotrophic factor (BDNF), insulin-like growth factor 1 (IGF-1), vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), platelet-derived growth factor AA (PDGF-AA), -AB and -BB, basic fibroblast growth factor (bFGF or FGF-2), bone morphogenetic protein 2,4,6 (BMP-2,-4,-6), hepatocyte growth factor (HGF), connective tissue growth factor (CTGF), chemokine (CXC) ligand12 (SDF-1), CXCL10, CXCL5, CXCL4 (PF4), CXCL3, CXCL2, CXCL1, and inflammatory cytokines such as: interferonγ (IFN-γ), tumor necrosis factorα (TNF-α), granulocyte-macrophage colony-stimulating factor (GM-CSF), granulocyte-colonystimulating factor (G-CSF), interleukin8 (IL-8), IL-7, IL-6, IL-1a, macrophage inflammatory protein 1a (MIP-1a), and MIP-1b. All are involved in differentiation, proliferation, angiogenesis, ulcer closure, and repair [7][8][9][10][11]. Leotot et al (2013), in an animal model, found that the mesenchymal stromal cells seeded on PL, coated with the hydroxyapatite/ b-tricalcium phosphate, enhanced vascularization and bone formation in mice [12].…”
Section: Pl/vancomycin/nano-hydroxyapatite Preparation and Characterimentioning
confidence: 99%